2017
DOI: 10.1016/j.otsr.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

First-line management of distal humerus fracture by total elbow arthroplasty in geriatric traumatology: Results in a 21-patient series at a minimum 2 years’ follow-up

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…15,16) Patient satisfaction rate was used for qualitative assessment and was described in only 4 studies. 13,14,18,20) The average value of postoperative flexion-extension motion arc reported in all studies was 102.3°. Only 7 studies described the postoperative pronation-supination motion arc, the average of which was 145.8°.…”
Section: Surgical Characteristicsmentioning
confidence: 88%
See 4 more Smart Citations
“…15,16) Patient satisfaction rate was used for qualitative assessment and was described in only 4 studies. 13,14,18,20) The average value of postoperative flexion-extension motion arc reported in all studies was 102.3°. Only 7 studies described the postoperative pronation-supination motion arc, the average of which was 145.8°.…”
Section: Surgical Characteristicsmentioning
confidence: 88%
“…The current systematic review showed that most of the patients were in their 7th decade of life (71.7%). Most of the studies included the closed fracture type (183 patients, 71.7%) [11][12][13][14][15]18,20) and a small number of open fracture type (18 patients, 7.05%), 14,15,17,20) whereas 54 cases (21.3%) did not specify the type of fracture. 16,19) In the elderly patients who have "paper thin" skin, the presence of a low-grade open fracture is not uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations